Alteration of the immune environment in bone marrow from children with recurrent B cell precursor acute lymphoblastic leukemia. Issue 1 (29th November 2021) - Mikami, Takashi; Kato, Itaru; Wing, James Badger; Ueno, Hiroo; Tasaka, Keiji; Tanaka, Kuniaki; Kubota, Hirohito; Saida, Satoshi; Umeda, Katsutsugu; Hiramatsu, Hidefumi; Isobe, Tomoya; Hiwatari, Mitsuteru; et al.
Abstract: Due to the considerable success of cancer immunotherapy for leukemia, the tumor immune environment has become a focus of intense research; however, there are few reports on the dynamics of the tumor immune environment in leukemia. Here, we analyzed the tumor immune environment in pediatric B cell precursor acute lymphoblastic leukemia by analyzing serial bone marrow samples from nine patients with primary and recurrent disease by mass cytometry using 39 immunophenotype markers, and transcriptome analysis. High‐dimensional single‐cell mass cytometry analysis elucidated a dynamic shift of T cells from naïve to effector subsets, and clarified that, during relapse, the tumor immune environment comprised a T helper 1‐polarized immune profile, together with an increased number of effector regulatory T cells. These results were confirmed in a validation cohort using conventional flow cytometry. Furthermore, RNA transcriptome analysis identified the upregulation of immune‐related pathways in B cell precursor acute lymphoblastic leukemia cells during relapse, suggesting interaction with the surrounding environment. In conclusion, a tumor immune environment characterized by a T helper 1‐polarized immune profile, with an increased number of effector regulatory T cells, could contribute to the pathophysiology of recurrent B cell precursor acute lymphoblastic leukemia. This information could contribute to the development of effective immunotherapeutic approaches against B cell precursor acute lymphoblastic leukemia relapse. Abstract : Tumor immune environment characterized by a T helper 1‐polarized immune profile was observed in recurrent B cell precursor acute lymphoblastic leukemia. Regulatory T cells were activated in recurrent B cell precursor acute lymphoblastic leukemia.